2020
DOI: 10.1142/s0219649220500252
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Financial Management on Improving Quality at Jordanian Public University Hospitals

Abstract: The main purpose of this study was to investigate the impact of financial management on improving quality at the public university hospitals in Jordan. We used a quantitative method with a sample of 220 public university hospital staff. Using simple linear regression analysis, we showed via our findings a significant impact of the financial management dimension on the quality management dimension. These findings emphasise that using a proficient financial management system would improve the quality of services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
2
0
2
Order By: Relevance
“…Al Raoush et al (2020) identificaram o impacto da gestão financeira na gestão da qualidade em hospitais universitários, para isso foi realizado um estudo em dois hospitais em regiões diferentes da Jordânia e foi utilizado como instrumento de pesquisa um questionário contendo questões de gestão financeira e gestão da qualidade hospitalar. O estudo revelou que existe um impacto estatisticamente significativo da gestão financeira na gestão da qualidade, devendo os hospitais universitários enfatizar o papel da gestão do setor financeiro e assim utilizá-lo para obter eficiência nos serviços.…”
Section: Práticas De Gestão De Qualidade Desempenho E Melhoria De Ind...unclassified
See 1 more Smart Citation
“…Al Raoush et al (2020) identificaram o impacto da gestão financeira na gestão da qualidade em hospitais universitários, para isso foi realizado um estudo em dois hospitais em regiões diferentes da Jordânia e foi utilizado como instrumento de pesquisa um questionário contendo questões de gestão financeira e gestão da qualidade hospitalar. O estudo revelou que existe um impacto estatisticamente significativo da gestão financeira na gestão da qualidade, devendo os hospitais universitários enfatizar o papel da gestão do setor financeiro e assim utilizá-lo para obter eficiência nos serviços.…”
Section: Práticas De Gestão De Qualidade Desempenho E Melhoria De Ind...unclassified
“…Os resultados desta categoria de análise vão ao encontro do estudo de Al Raoush et al (2020), os quais identificaram a importância de realizar o acompanhamento e monitoramento dos indicadores de desempenho para o sucesso da prestação do serviço de saúde.…”
Section: Política Da Qualidadeunclassified
“…Al Raoush et al (2020) identified the impact of financial management on university hospitals' QM. They carried out research in two hospitals in different regions of Jordan and applied a questionnaire on financial management and hospital quality management.…”
Section: Quality Management Practices Performance and Improvement Of ...mentioning
confidence: 99%
“…However, financial managers at hospitals should be qualified and have special knowledge and skills in order to face the fast and dynamic changes in health care services. Financial management helps hospital managers to make rational financial and administrative decisions and choose effective methods for spending money (Al Raoush, A'aqoulah, Albalas, & Athamneh, 2020). Most of the payments made to hospitals for patient services are made by government programmes or commercial insurance companies.…”
Section: Introductionmentioning
confidence: 99%